The Effectiveness of Constructive Learning Model in the achievement of Students in the Fifth Grade Literary Literature and Texts and the Development of Dialogue Skills - Salman Al Nuaimi, Mohsen Mouloud (Opción, 2019)
The study aimed to identify the effectiveness of the constructional learning model in the achievement of the fifth grade students in the literature and texts and the development of the skill of dialogue. The research sample consisted of 59 students. The researcher compensated between the students of the two groups statistically in a number of variables. The researcher prepared a col- lection test in literature and texts The researcher prepared a measure of the skill of the dialogue, which consists of (39) paragraphs and has been verified the validity and stability, the researcher used statistical means in the research procedures and analysis of its results. The researcher concluded that the stu- dents of the experimental group excel in the achievement test and in the skill level of dialogue. The researcher recommended a number of recommenda- tions and suggested a number of proposals for subsequent studies.